Mechanical Properties of Sandstones under Initial Unloading Damage - Hengbin Zhang; Lehua Wang; Jianlin Li; Huafeng Deng; Xiaoliang Xu (Advances in Civil Engineering)
To study the influence of initial unloading damage on the mechanical properties of sandstone, the repeated loading test of unloading damaged sandstone was carried out considering 8 initial unloading quantities of 100%, 93.33%, 86.67%, 80%, 73.33%, 66.67%, 40%, and 0%. The results were compared with those of the triaxial compression test of intact samples. The results show that the peak strength of intact samples is higher than that of unloading damaged samples, and the difference is more obvious when the unloading quantity is more than 80%. During the unloading process, the strain increasing rate of rock samples is obvious, and the lateral dilatation is significant, and the deformation modulus and compressive strength of the rock sample deteriorate obviously. From the energy point of view, the greater the unloading damage, the smaller the stored elastic strain energy, which leads to the decrease of peak strength. At present, the unloading fracture inside the rock sample has developed, and the failure mode of the sample gradually changes from compression shear failure to tensile shear failure. In the process of engineering rock mass excavation, the unloading area and unloading damage amount of the rock mass is a dynamic adjustment process. To ensure the safety of the engineering rock mass, it is suggested to determine reasonable reinforcement time, reinforcement area, and reinforcement measures.